321 DESCRIPTION OF NOVEL POLYMORPHISMS IN THE CODING AND PROMOTER REGIONS OF THE MELANOCORTIN 4 RECEPTOR GENE IN AFRICAN AMERICANS. (1st January 2006) - Batra, A.; Marks, D. L.; Orwoll, E.; Cone, R. D.; Kaye, J.; Newcomb, K.; Purnell, J. Q.
Abstract : The melanocortin 4 receptor (MC4R) is an important part of a hypothalamic pathway involved in the normal regulation of body weight. Disruption of MC4R signaling by mutation or knockout leads not only to severe obesity in humans, but affected subjects are also taller, have greater lean mass, and have greater bone density than obese matched controls. The mechanism whereby disruption of the melanocortin pathway results in altered body composition and bone density is not known, but alteration in this pathway may affect the bone and muscle mass in populations other than obese subjects, including the elderly. In a pilot study, we have determined the prevalence of single nucleotide polymorphisms (SNPs) in the MC4R gene and its promoter in populations of older Caucasian ( n = 48), African American ( n = 48), and Hong Kong Chinese ( n = 48) men and women. The African American cohort had the highest prevalence of SNPs (33%) and the Chinese cohort the lowest (12%). A total of nine nucleotide substitutions were detected, six previously reported and three that are novel. The novel SNPs were found in the African American cohort; of which one is in the coding region (11C>T) and two are in the noncoding region (-337 A>C and -300 G>C). All variants detected in this study were in the heterozygous form except for the -337 A>C and -300 G>C polymorphisms. The subject with the 11C>T heterozygous SNP in the African American cohort had a BMI of 31.0 kg/m 2 at age 69.7, where the mean BMI for the cohort was 29.0 kg/m 2 with a range of 17.6 to 50.2 kg/m 2 . Of particular interest is that the 11C>T variant predicts a nonconserved amino acid change at codon 4 from a serine to phenylalanine. Further functional characterization will be needed to determine the impact of this amino acid change on MC4 signaling. Exploring the relationship between mutations in the MC4R gene and its promoter on differences in body composition in these populations potentially offers new insights into central nervous regulation of lean mass and bone density.